Service Economies : Militarism, Sex Work, and Migrant Labor in South Korea - Lee, Jin-kyung (Book collections on Project MUSE., 2010)
Service Economies presents an alternative narrative of South Korean modernity by examining how working-class labor occupies a central space in linking the United States and Asia to South Korea's changing global position from a U.S. neocolony to a subempire. Making surprising and revelatory connections, Jin-kyung Lee analyzes South Korean military labor in the Vietnam War, domestic female sex workers, South Korean prostitution for U.S. troops, and immigrant/migrant labor from Asia in contemporary South Korea.